Bike Attitudes Predict Behaviour Change, more than Vice Versa: A Norwegian Quasi-replication of Kroesen and Colleagues (2017) - Lars Even Egner; Hanne Beate Sundfør; Aslak Fyhri (Findings)
Existing research from the Netherlands suggests that bicycle attitudes and behaviour affect each other, but bicycle behaviour affects attitude more than vice versa (Kroesen et al., 2017). We conducted a quasi-replication study using existing datasets (n=972) with slightly different operationalisations and timeframes in a Norwegian context. Using two variations of a structural equation model, we confirm this bidirectional effect, though our findings show a considerably stronger influence of attitudes on behaviour than the reverse.